Class Construction: White Working-Class Student Identity in the New Millennium - Freie, Carrie (Lexington Books, 2007)
Class Construction explores class, racial, and gender identity construction among white, working-class students. Delving into River City High School, Freie asks what happens to the adolescent children of working-class families when economic changes such as globalization and technological advancements have altered the face of working-class jobs. Mass consumerism, greater availability of college level education, lack of a cohesive class identity, and racial and religious politics all combine to create a new working-class identity for today's youth. Featuring interviews with the River City High School students, Class Construction aims to understand how class is conceptualized among American, working-class youths. Class Construction is ideal for courses on sociology, education, gender studies, and American studies, as well as high school educators and administrators.